Catalog of the Bibliothèque Classique des Pianistes published in Paris by Schonenberger. - Schonenberger::::::::::::::: (Schonenberger; Paris; France, 2022)
Catalog of the Bibliothèque Classique des Pianistes published in Paris by Schonenberger, printed on the back cover of the piano arrangement of Beethoven's Septet, op. 20, from the Répertoire des Morceuax d'Ensemble éxécutés par la Société des Concerts du Conservatoire.